Exploration of Local Values in Arabica Coffee Farming Practices in the Roasting Process in Rural Areas of Enrekang Regency, South Sulawesi - Firsyah Vani Ameliza; Irmayani Irmayani; Irninthya Nanda Pratami Irwan (International Journal of Business and Quality Research, 2025)
Coffee is a strategic commodity that contributes significantly to Indonesia's national economy. However, most of Indonesia's coffee exports are still in the form of raw beans (green beans), so the added value of the product has not been optimally felt by the local farming community. This study aims to examine the practice of community-based coffee roasting developed by the people of Bone-Bone Village, Baraka District, Enrekang Regency, as a strategy for downstreaming local coffee products and economic empowerment based on regional potential. The method used is a qualitative approach with case studies, through participatory observation, in-depth interviews, and documentation. The results of the study show that the roasting practice in this village is carried out traditionally with techniques that are inherited from generation to generation, but are able to produce competitive distinctive flavors. The community utilizes social capital in the form of trust and collaboration in maintaining the quality of products collectively. Despite facing challenges such as limited infrastructure and technology, the practice demonstrates local resilience and innovation in coffee processing. The results of this study conclude that community-based roasting practices have the potential to increase economic value and strengthen local cultural identity, and are suitable as a replication model for the development of the coffee industry in other regions.